LEARNING MANAGEMENT SYSTEM BERBASIS CLOUD SEBAGAI ALTERNATIF PEMBELAJARAN BAGI GURU SEKOLAH MENENGAH PERTAMA - Hansi Effendi; Nurindah Dwiyani (Jurnal Teknologi Informasi dan Pendidikan, 2018)
The purpose of this paper is to see an increase in the knowledge of Majelis Guru Mata Pelajaran (MGMP) of Kabupaten Lima Puluh Kota after a training of Cloud-based Learning Management System (LMS) using Moodlecloud and ask their opinions about the use of LMS in learning in their Subjects. The experimental design used to see the increase in the knowledge of the participants in this training was pre-experimental using the one-group pre-test post-test design. The teachers involved in the training were 15 people. Their opinion on the use of LMS for learning was asked through a questionnaire. The data shows that there is an increase in the teacher's knowledge in managing LMS using Moodlecloud, and from the questionnaire it appears that they agree that the use of LMS in their learning is interesting, practical, motivating and easy to use. From the interviews, it was also concluded that they were very enthusiastic in using this media as an additional alternative to their respective subject learning